KEBIJAKAN HUKUM PIDANA TERHADAP PELAKU YANG MELAKUKAN KEKERASAN DIHADAPAN ANAK - Herlina, Herlina; Alfonsus Hendri Soa; Fitri Hertini , Mega (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The current legal provisions do not yet regulate matters related to children’s mental development, for example in cases of violent crimes where the position of children is as a witness. There have not been many studies on criminal law policies towards perpetrators who commit violent crimes against children. This research aims to find out the current policy formulation regarding perpetrators who commit crimes of violence in the presence of children using normative legal research methods which focus on research on the substance of the law, namely on the law currently in force (ius constitutum) and the desired law. aspire (ius constituendum). Regarding policies towards perpetrators who commit violence in front of children in future criminal law, whether in the Criminal Code, the Child Protection Law, the Law on the Elimination of Domestic Violence, the Human Rights Protection Law, the Victim Witness Protection Law, have not yet accommodated acts of violence committed by perpetrators in front of children. specifically (special article), for example, for this act there are criminal penalties that must be imposed on the perpetrator considering that the incident witnessed by the child greatly affects the child’s mental health and it is possible that the child’s mental health will become disturbed